Walking the tightrope : genomic characterization of the bumblebee Bombus atratus in Colombia (2019)
In recent years, habitat loss and climate change have been one of the main causes of the decline of pollinator insects of high importance. However, one of the most affected groups has been the bumblebees of the genus Bombus. In Colombia, the dynamics and processes of dispersion of these species in landscapes affected by humans remain unknown. Since the change in habitat can increase intrinsic threats to populations, including genetic drift and inbreeding, the use of molecular tools in conjunction with population genetics is essential to understand the most basic levels of biological diversity, and identify the genetic status of populations affected by changes in the landscape. We examine the patterns of genetic diversity and how environmental factors can shape it through the use of NextRAD, in a population of bumblebees of the species Bombus atratus, which has a range of distribution that overlaps highly agricultural ecosystems. Our results reveal a low genetic differentiation among sample localities, suggesting a low effect of land use on genetic flow. However, we found a negative correlation between genetic diversity and land use, this indicated that environmental variables at the local level are what are shaping genetic variations. We identified several loci under selection, a subset of which was associated with land use, taken as the percentage of surface surrounding each sampling site. Our findings shed important light on the life history of B. atratus and highlight the role of land use as a phenomenon of change regarding the genetic diversity of these bumblebees. Likewise, our research reveals for the first time patterns of local adaptation in this species in Colombia.